CLINICAL EPIDEMIOLOGY OF DOMESTIC AND INDUSTRIAL HAND AND WRIST CIRCULAR SAW INJURIES - Pantelić, Anđela; Gambiroža, Katarina; Matić, Slađana; Tulić, Goran (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Hand injuries are extremely common. It is estimated that almost a quarter of all injuries treated in the emergency department are hand injuries, due to the fact that the hand is highly exposed to trauma, as the result of its function and its protective movement. These injuries are usually seen in the young working age population, and they involve simultaneous damage to several different tissues.Aim: The purpose of this study is to evaluate the frequency and characteristics of hand injuries sustained by the circular saw, as well as to assess existing risk factors, in order to improve the prevention of these injuries.Materials and methods: This is a retrospective study involving 365 patients, treated during a five-year period. The patients suffered hand injury with a circular saw, either at home or at work. All patients were surgically treated at a single medical center. The patients were mostly men, with an average age of 48.6 ± 14.71 years. The data, which was collected from the medical records, included localization and type of injury, dominance of the injured hand, the type of surgical procedures performed, and the length of hospital stay.Results: The non-dominant hand was injured more often (62%), and this was usually the left hand (60%). The majority (83.2%) of patients were injured at home, while significantly less patients were injured in the workplace (16.7%). Most often, the patients sustained injuries to several different tissues, while there were only 12.5% ​​of isolated injuries. The most commonly injured structures were extensor tendons of the wrist and fingers (245), followed by phalanges (226). Most of the patients sustained injury to one finger (35.1%), especially the thumb (68.4%), while two fingers were injured in 35.1% and three fingers in 20% of cases. The hand was injured in 7.27% of the cases, and the forearm was injured in 5.45% of the cases. Of the 995 surgical procedures carried out in total, the most commonly performed operation was tenorrhaphy (44.67%), followed by fracture fixation (29.3%). Finger reamputation was performed in 6.67% of cases, neurorrhaphy in 6%, and tendon reinsertion in 4% of cases. There was a total of 46 replantations (4.67%), and 27 revascularizations (2.67%). The average length of hospital stay was 9.04 ± 3.91 days.Conclusion: Working with a circular saw is a high-risk activity. The injuries sustained are severe. They can result in significant functional deficit and have major socioeconomic consequences. Lack of prior training and improper handling are clear risk factors. Clinical and epidemiological analysis is therefore of extreme importance, as it can be the key to the prevention of these injuries.
Keywords: hand injury; circular saw; prevention